To compare the expression, processing, incorporation and function of pseudoviruses and infectious molecular clones using different cell types and HIV backbones - Abrahams, Bianca (Department of Integrative Biomedical Sciences (IBMS), 2020)
Understanding HIV transmission mechanisms is essential for the design and development of an efficacious, broadly acting vaccine that targets features common to transmitted viruses. However, there is a lack of consensus amongst current HIV studies characterising transmitted founders (TFs). When investigating the methods employed across studies, it becomes clear that methodologies are highly variable and thus, could be impacting research outcomes. This study therefore aimed to determine whether Envelope (Env) expression and processing affects function and whether cell type and/or expression system were responsible for these differences. Our data suggest that even though we did not observe differential expression of recombinant Env clones across cell types, when pseudovirus and infectious molecular clone (IMC) backbones were introduced, expression of Env decreased. We also found differences in processing in the form of cleavage, N-glycosylation and incorporation of Env across cell types. We conclude from this that methods used to study Env characteristics are highly sensitive to cell type and HIV backbone which suggests that a more standardised system is required to make meaningful comparisons between studies. The results of our functional Env analysis revealed high variation depending on the methodology used. We found that entry of TZM-bl cells by pseudovirus (PSV) is dependent on the cell line used to produce the viral particles. Unfortunately, due to low IMC titre, we had to expand the virus in PBMCs, negating the effect that cell type might have had on IMC expression. We could thus not directly compare PSVs to IMCs. However, PSV and IMC entry as well as IMC replication in PBMCs suggested that CHO cells were not suitable for robust viral production and better suited for recombinant Env expression. Overall, the findings in this project support previous findings that PSVs and IMCs are not directly comparable due to multiple factors that influence Env expression and virus production. We suggest that researchers who focus on HIV functional analysis, particularly Env, with the end-point of informing vaccine design, need regulated methods across laboratories, similar to the way that neutralisation assays were standardised.